ZIF-8 pyrolized N-doped carbon-supported iron catalysts for enhanced CO2 hydrogenation activity to valuable hydrocarbons - Deng, Chao; Wang, Xu; Chen, Xixi; Gao, Ruxing; Zhang, Leiyu; Zhang, Chundong; Jun, Ki Won; Kim, Seok Ki; Wan, Hui; Guan, Guofeng (Catalysis Science and Technology, 2024)
N-doped carbon (NC) material-supported Fe catalysts have been widely used in CO2 hydrogenation reactions; however, the interaction between iron active sites and NC supports is still unclear. Herein, we synthesized a series of ZIF-8-derived N-doped carbon-supported iron catalysts via varied pyrolysis temperatures (Fe/NC-T, T = 950, 1050 and 1150 °C), preserving different amounts of N-type and C-type and tunable surface N-content. N-doping increases the adsorption of CO2 and the electron density around the active phase Fe, thereby enhancing the dissociation of CO2 during the reaction and the subsequent conversion of the CO intermediate to the hydrocarbon product. Besides, the balance of surface N-containing pyrrolic and graphitized carbon-mediated electron transfer on the catalyst surface was responsible for the enhanced catalytic performances. XPS, Raman spectroscopy, and TPD techniques were used to verify these alterations. The findings of this study provide insights and guidance for optimizing the catalytic performance of N-doped carbon-supported Fe catalysts in CO2 hydrogenation reactions.
Keywords: Active site; Carbon material; Carbon support; Catalytic performance; Doped carbons; Hydrogenation activity; Hydrogenation reactions; Iron catalyst; N-doped; Supported Fe catalyst